Relationship of risk perception and beliefs with drug use in Nursing Teachers - Mateo Crisóstomo, Yadira (2022)
Objective: Examine the prevalence of alcohol, tobacco and medical drug use and determine the relationship of risk perception, beliefs of teachers with drugs consumption. Methods: Quantitative study with a descriptive, correlational and inferential design. The population studied was made up of nursing professors from the State of Tabasco, Mexico. Sampling was non-probabilistic for convenience; the sample was 60 participants. To measure the perception of risk towards tobacco and alcohol consumption, the Risk Perception Questionnaire for the Consumption of Licit Drugs and the Scale of Education in Nursing in Alcohol were used. Results: In the subscales of risk perception on the consumption of alcohol, tobacco and medical drugs, the following data is presented at a moderate level; negative consequences of alcohol consumption (75%), negative consequences of tobacco use (66.7%) and negative consequences of medical drug use (73.3%). With regard to beliefs about the consumption of alcohol, tobacco and medical drugs, it is shown tan 70% have positive beliefs about drug use. A positive and significant relationship was found between risk perception and beliefs (rs = .359, p = .005). Conclusion: The higher the risk perception of nursing teachers, the better will be the positive beliefs about drug use.